EFFECT OF CULTURE ON BALINESE LANGUAGE USED BY EMPLOYEE HOTELS FOR FOREIGN TRAVELERS IN THE SOCIOLINGUISTIC PERSPECTIVE - Redianis, Ni Luh; Putra, Anak Agung Bagus Mutiara Arsana; Anggayana, I Wayan Agus (International Conference on Cultural Studies, 2019)
This study aims to find out the relationship between language and culture in hotels industry. The instruments used in this study were (a) diaries (b) interview guidelines, (c) cameras. Observation methods, interview techniques and documentation in the form of recorded speeches while conducting research Subordinate relations reflect one quality relationship that is only unilateral, meaning that the cultural dynamics influence the dynamics of the balinese language community. This is evidenced by the relationship that states language is the result of culture when compared to balinese language. This is influenced by foreign tourists visiting the balinese community in hotels industry.